2013
DOI: 10.1016/j.bbr.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anti-murine Aβ immunization preserves odor guided behaviors in an Alzheimer's β-amyloidosis model

Abstract: Olfaction is often impaired in Alzheimer‟s disease (AD) and is also dysfunctional in mouse models of the disease. We recently demonstrated that short-term passive anti-murine-Aβ immunization can rescue olfactory behavior in the Tg2576 mouse model overexpressing a human mutation of the amyloid precursor protein (APP) after β-amyloid deposition. Here we tested the ability to preserve normal olfactory behaviors by means of long-term passive anti-murine-Aβ immunization. Seven-month-old Tg2576 and non-transgenic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
5
4
0
Order By: Relevance
“…Guerin et al (2009) using the often employed Tg2576 mouse found no apparent odor detection deficits but pronounced odor habituation changes at 7 months of age despite a lack of Aβ accumulation in any brain region. Our group using the same mouse model found similar results in odor habituation beginning at 6 months of age (Wesson et al, 2010, 2011, 2013). Preventing or reversing the Aβ accumulation restored normal odor habituation (Cramer et al, 2012; Morales-Corraliza et al, 2013; Wesson et al, 2011, 2013; Yang et al, 2011), while inducing damage to the locus coeruleus noradrenergic system exacerbated them (Rey et al, 2012).…”
Section: Olfactory Cortex and Pathologysupporting
confidence: 65%
See 1 more Smart Citation
“…Guerin et al (2009) using the often employed Tg2576 mouse found no apparent odor detection deficits but pronounced odor habituation changes at 7 months of age despite a lack of Aβ accumulation in any brain region. Our group using the same mouse model found similar results in odor habituation beginning at 6 months of age (Wesson et al, 2010, 2011, 2013). Preventing or reversing the Aβ accumulation restored normal odor habituation (Cramer et al, 2012; Morales-Corraliza et al, 2013; Wesson et al, 2011, 2013; Yang et al, 2011), while inducing damage to the locus coeruleus noradrenergic system exacerbated them (Rey et al, 2012).…”
Section: Olfactory Cortex and Pathologysupporting
confidence: 65%
“…Our group using the same mouse model found similar results in odor habituation beginning at 6 months of age (Wesson et al, 2010, 2011, 2013). Preventing or reversing the Aβ accumulation restored normal odor habituation (Cramer et al, 2012; Morales-Corraliza et al, 2013; Wesson et al, 2011, 2013; Yang et al, 2011), while inducing damage to the locus coeruleus noradrenergic system exacerbated them (Rey et al, 2012). Finally, in a test of hippocampal-dependent odor memory, Young et al (2009) found that as Tg2576 aged, they were able to remember fewer odors and made more errors in an odor span task designed to assess working memory for 12–22 odors.…”
Section: Olfactory Cortex and Pathologysupporting
confidence: 65%
“…Since PC encodes higher-order representations of odor quality, identity, and familiarity [41], and is associated with olfactory learning and memory, disrupting PC activity would impair corresponding olfactory functions [14]. Along with the facts that A␤-dependent olfactory dysfunction occurs in young Tg2576 mice [61] and normal odor-guided behaviors are preserved by long-term A␤ oligomer antibody treatment [62], our results suggest that soluble A␤ aggregates in olfactory cortices play an important role in early olfactory deficits.…”
Section: Aβ Aggregation In the Olfactory Cortices And Development Of supporting
confidence: 61%
“…This pathological olfactory circuit hyperactivity emerges by 6 months of age, which corresponds with deficits in olfactory habituation in early age groups [15], [20]. Furthermore, reducing soluble Aβ levels in a variety of ways restores olfactory cortical physiology and olfactory habituation [14], [20][22].…”
Section: Introductionmentioning
confidence: 99%